Exploring sports participation, self-esteem and life satisfaction among university students - Saw, Keith Hui-Xun (Nanyang Technological University, 2020)
Background: University students face high levels of academic stress. Recent data found low sports participation among the age group where most university students fall under. The purpose of this paper is to address the impact of sports participation on a university student’s self-esteem and life satisfaction. It is hypothesized that university students that participate in sports have higher self-esteem and life satisfaction than non-sports participants, and self-esteem has a significant relationship with life satisfaction. Methods: The study is a cross-sectional study design. The participants in this study includes 90 students from Nanyang Technological University, Singapore. Participants were recruited through stratified sampling, with two group identified as university team athletes and non-sports participants. Two questionnaires were given to the participants; the Rosenberg Self-Esteem Scale (RSES) and the Satisfaction with Life Scale (SWLS) to measure the level of global self-esteem and life satisfaction among the participants, respectively. The questionnaire will also include the participants’ sports participation level and age. Results: The results show no significant difference between university team athletes and non-sports participants in self-esteem scores, as well as life satisfaction scores. Significant correlation was found between in self-esteem and life satisfaction. Conclusion: This study concluded that no significant difference was found between university team athletes and non-sports participants in self-esteem and life satisfaction scores. However, the results found should not discount the possibility that the element of sports participation may aid an individual’s self-esteem and life satisfaction. Higher self-esteem may lead to higher life satisfaction.